Revisiting decompression sickness risk and mobility in the context of the SmartSuit, a hybrid planetary spacesuit - Logan Kluis; Ana Diaz-Artiles (npj Microgravity, 2021)
Abstract Gas pressurized spacesuits are cumbersome, cause injuries, and are metabolically expensive. Decreasing the gas pressure of the spacesuit is an effective method for improving mobility, but reduction in the total spacesuit pressure also results in a higher risk for decompression sickness (DCS). The risk of DCS is currently mitigated by breathing pure oxygen before the extravehicular activity (EVA) for up to 4 h to remove inert gases from body tissues, but this has a negative operational impact due to the time needed to perform the prebreathe. In this paper, we review and quantify these important trade-offs between spacesuit pressure, mobility, prebreathe time (or risk of DCS), and space habitat/station atmospheric conditions in the context of future planetary EVAs. In addition, we explore these trade-offs in the context of the SmartSuit architecture, a hybrid spacesuit with a soft-robotic layer that, not only increases mobility with assistive actuators in the lower body, but it also applies some level of mechanical counterpressure (MCP). The additional MCP in hybrid spacesuits can be used to supplement the gas pressure (i.e., increasing the total spacesuit pressure), therefore reducing the risk of DCS (or reduce prebreathe time). Alternatively, the MCP can be used to reduce the gas pressure (i.e., maintaining the same total spacesuit pressure), therefore increasing mobility. Finally, we propose a variable pressure concept of operations for the SmartSuit spacesuit. Our framework quantifies critical spacesuit and habitat trade-offs for future planetary exploration and contributes to the assessment of human health and performance during future planetary EVAs.